The death and return of Bibframe - Martínez-Ávila, Daniel (Anuario ThinkEPI, 2023)
In this text I present a brief review of the critiques of MARC and its replacement proposals based on semantic technologies and linked (open) data, focusing mainly on Jeff Edmunds’ recent critique titled Bibframe must die. Edmunds’ arguments are presented and analyzed in addition to some of the responses published on the Bibframe mailing list, including contributions by Karen Coyle, Shawne Miksa, and others. I conclude with the need to deepen the use and dissemination of semantic technologies on the basis of linked (open) data such as Bibframe to achieve a better representation of knowledge in the era of big data and artificial intelligence inferences, as these are aspects that are designated by Edmunds as the future of representation in cataloguing.
Keywords: Bibframe; MARC; Linked (open) data; Cataloguing